A flavone C-Glycoside from Styela plicata. (October 2019) - Shi, Xiaohui; Xu, Changan; Wu, Chang-Jer; Wu, Xiuna; Zhang, Bo; Tang, Xu; Luo, Lianzhong; Chen, Yung-Husan
Abstract: A known flavonoid triglycoside, apigenin 6-C-[ α -L -arabinopyranosyl-(1‴→2″)- β -D -glucopyranoside]-7-O- β -D - glucopyranoside (1 ), was isolated from the n -butanol extract of Styela plicata for the first time. The structure of1 was established by spectroscopic methods and direct comparison with authentic samples on HPLC after acid hydrolysis as a new marine natural flavonoid. This work contributes to expand the knowledge about the chemical compositions of S. plicata and the chemotaxonomy of ascidians. Graphical abstract: Image 1 Highlights: A known flavone C-glycoside was isolated for the first time from Styela plicata . The isolation of1 enriches the chemical compositions of S. plicata . The isolation of 1 contributed to the chemical diversity of marine flavonoids.